THERMAL ENERGY STORAGE INTEGRATION MODELING FOR INCREASED FLEXIBILITY OF POWER PLANT - Ajie Widyaseno Putra, Ruth
The energy transition is a problem that's being intensively discussed by many countries to eliminate dependence on fossil energy. Most of the fossil energy users come from the electricity generation process which uses coal as the main fuel. To expedite the energy transition, this can be done by integrating renewable energy with power plants that have been used in the context of energy transformation towards emission-free clean energy. Flexible, safe, and reliable power plants are an important aspect of integrating intermittent renewable energy, such as solar and wind energy. In this study, increasing the performance of the power plant to make it more flexible is done by dynamic simulation. The power plant model was generated using Dymola software with the Cla-Ra library. In this simulation, integration of Thermal Energy Storage (TES) is carried out in the simulation model to increase the flexibility parameters of the plant such as minimum load and ramp rate. The simulation results showed increasing flexibility of the power plant by integrating TES into the generator model. The potential for reducing the minimum operating load is 2.87 – 4.62% and increasing the ramp rate by 29.5% from the nominal time. Then, at minimum load operation, there is a minimum load reduction potential of 2.87 – 4.62% and an increase in ramp rate of 40% due to TES integration. TES integration has an impact on increasing the operating flexibility of the power plant.